Archives and Absence: The Role of the Institutional Archive in Retaining Cultural Memory (Part 1) - Denison, Veronica; Egbert, Helena; Rogova, Irina (My University, 2021)
Presented during American Archives Month, archivists Veronica Denison, Helena Egbert, and Irina Rogova from K-State Libraries’ Morse Department of Special Collections offer the first in a series of three talks inspired by the themes of community and memory in The Marrow Thieves by Cherie Dimaline. Part 1: Why are there so few materials from folks of marginalized identities in institutional archives?
Keywords: Marrow Thieves, The; Common reading program; First-year experience program; Archives; Marginalized identities; Community and memory